2014
DOI: 10.1080/00140139.2014.938129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foot orthosis customisation on perceived comfort during running

Abstract: The perceived level of comfort of footwear is considered to be a protective measure of the potential risk of running injuries. We here compared runners' perception of comfort of custom-made and prefabricated orthoses while running. We found that even though custom-made orthoses are closely matched to each individual's foot, such customisation does not necessarily imply greater comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…These findings suggest that compressive stockings may play a protective role by reducing impact accelerations during running. may ultimately influence their performance [25,31]. Comfortable garments require the absence of pain and discomfort, which has been reported to occur before the onset of injuries [46].…”
Section: Abstract ▼mentioning
confidence: 99%
See 3 more Smart Citations
“…These findings suggest that compressive stockings may play a protective role by reducing impact accelerations during running. may ultimately influence their performance [25,31]. Comfortable garments require the absence of pain and discomfort, which has been reported to occur before the onset of injuries [46].…”
Section: Abstract ▼mentioning
confidence: 99%
“…Comfortable garments require the absence of pain and discomfort, which has been reported to occur before the onset of injuries [46]. It has been suggested that comfort is a prerequisite for the reduction of injury-related complaints and a key factor to take into account when analysing the effectiveness of sport garments on running performance and their influence on injury occurrence [31,41]. Most of the studies have analysed the acute effects of graduated compressive stockings after an acute intervention [9,15,26].…”
Section: Abstract ▼mentioning
confidence: 99%
See 2 more Smart Citations
“…The second frequently-used word is "biomechanics". It states that some studies in ergonomic design assess quantitatively the impact of the biomechanical factors on the risk of injury to control occupational injuries [31].The nodes such as "musculoskeletal disorders", "postures", "fatigue", "mental workload", "low back pain", "comfort", "heart rate" and "safety" continuously appear as red nodes in co-word networks, and their size have kept stable in the past 12 years, which reveals that they are the core themes during 2004-2015. It suggests that due to the increasingly complex technology, the increment of work activities required of people is leading to a broader range of physical stress, as well as psychological stress.…”
Section: Identifying Research Trends With Network Analysismentioning
confidence: 99%